Ex Vivo Human Placental Transfer of Trovafloxacin - Brian Casey; Roger E. Bawdon (Hindawi Limited, 2000)
Objective: The purpose of this study was to determine the ex vivo human placental transfer of trovafloxacin from the maternal circulation to the fetal circulation.